IMPROVING URBAN BUS SERVICE REGULARITY THROUGH OPTIMIZATION OF PLANNED HEADWAYS ON CITY BUS ROUTES (Ustozlar uchun, 2026)
Ensuring regular bus movement on urban routes is one of the key conditions for improving the quality and efficiency of public transport services. In practice, even when the route infrastructure and rolling stock are satisfactory, irregular operation often arises due to an incorrect choice of planned headway. If the headway is too short, buses tend to bunch under variable traffic conditions; if it is too long, passenger waiting time increases and the route becomes less attractive. Therefore, the problem of determining an optimal headway that balances operational stability and passenger service quality is of considerable practical importance. This paper develops an improved mathematical model for optimizing planned headways on urban bus routes in order to increase service regularity. The proposed approach is based on minimizing the weighted sum of headway deviation, passenger waiting cost, and operating cost under fleet-size and cycle-time constraints. A computational experiment was conducted for a model urban route under several headway scenarios. The results showed that reducing the planned headway from 14,0 minutes to 10,0 minutes improved the regularity level from 78,4% to 87,6%, while a further reduction to $8,0$ minutes led to increased bunching risk and a decrease in stability. The optimal headway for the studied conditions was found to be 10,0 minutes. The developed model can be used in timetable design, dispatch planning, and operational adjustment of urban bus routes.